PELATIHAN PENANGANAN DEFACE PADA PT.CLOUD HOSTING INDONESIA - Nurjaman, Muhammad Fadilah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The purpose of this training program was to enhance the skills of interns at PT. Cloud Hosting Indonesia in addressing website defacement issues, particularly on WordPress platforms. The training focused on understanding cyber threats, specifically deface attacks, and hands-on practices in managing index and .htaccess files to improve website security. The results showed that participants successfully learned to identify security vulnerabilities and apply solutions such as disabling unnecessary directory indexing, securing sensitive files, and enforcing HTTPS protocols. This training effectively equipped participants with the necessary skills to prevent and address defacement on WordPress websites